IMPLEMENTASI PP NO. 27 TAHUN 1998 TENTANG PENGGABUNGAN PELEBURAN DAN PENGAMBILALIHAN PERSEROAN TERBATAS DENGAN BERLAKUNYA UU NO. 40 TAHUN 2007 - Sukirman Sukirman (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Incorporated Company is one of the most preferred form of the Company by Entrepreneur and holds an important role in mobilizing the National Economic Development. To develop incorporated company to become a healthy business, can be reach by the expansion that can be done through Merger, Consolidation and Acquisition. From those three forms, takeovers is considered more practical and profitable for the company to develop their business, because there are no company that merged or disbanded. In the implementation, the enactment of Law Number 40 Year 2007 concerning Incorporated Company are not followed by the promulgation of Regulation of the implementation of the Act. This causes the interested parties still refer to the former regulations. The problems that arise is how the implementation of Government Regulation No.27 year 1998 about Merger, Consolidation, and Acquisition of Limited Liability Company with the enactment of Law No.40 Year 2007. Based on the analysis, it known that the enactment of Law No.40 Year 2007 concerning Incorporated Company, Government Regulation No.27 Year 1998 concerning Merger, consolidation, and Acquisition still in force. In addition, Merger, consolidation, and acquisition is still based on Government Regulation No.27 Year 1998 and Article 134 of Company Law.Keywords: Merger, Consolidation, and Acquisition.